International Seminar Developing Society 5.0 Skills in The New Era Transformation of Indonesian IPS Education in The 21st Century - Siti Aminah (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2021)
Transformation is a modernization challenge that is familiar to the Indonesian people. This transformation is a process towards newer changes and must be responded to by all social and educational people to achieve quality changes to the times. This response resulted in multifunctional changes in community life and the educational environment. However, the 21st century is still weak in a positive response to the transformation of the times, so it appears to have negative impacts such as a lack of interest in the social environment. So the role of multifunctional education, namely PIPS, is a means for the nation's children to learn in the social world. The purpose of this article is to describe the transformation of social science education in Indonesia in the 21st century. The method of writing articles is described through literature studies that use search engines to obtain journals and ebooks. The discussion described in this article includes how the transformation of social studies education changes in Indonesia in the 21st century, reflecting on the beginning of education known to Indonesia.